Early Onset Diabetes in Two Children due to Progeria, a Monogenic Disease of DNA Repair - Martin Holder; Valerie Schwitzgebel (Galenos Yayincilik, 2020)
Progeria syndrome is a rare disorder in childhood which causes accelerated systemic aging. Due to the accelerated aging process, disorders which normally occur only in old age will appear in these children at a much younger age. We report two children with progeria syndrome, in whom fulminant diabetes mellitus manifested at a very early age.